Current knowledge of the Łódź Upland avifauna - Markowski, Janusz; Wojciechowski, Zbigniew; Markowska, Maria; Janiszewski, Tomasz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
The authors evaluated the state of the knowledge of the Łódź Upland (about 18 000 km 2) avifauna. The total of 278 bird species was recorded by authors in the study area since the last century. After 1945, the total of 267 species were recorded, including 180 breeding species. According to the authors’ estimates about 11% of the area was investigated more preciously. The best investigated regions are: the Bzura river valley, 219 species were recorded including 165 breeding ones, the Pilica river valley, where the respective values are 211 and 158, region of the Jeziorsko Reservoir - 247 observed species and 152 breeding ones, the vicinities of the locality of Rogów with 118 breeding species and the Łódź city area with 125 breeding species. The Łódź Upland has been the place o f breeding for some rare birds in Poland: Cormorant, Purple Heron, Lesser Spotted Eagle, Hen Harrier, Montague’s Harrier, Curlew, Ruff, Herring Gull, White-winged Tern, Whiskered Tern, Crane, Stonechat, Collared Flycatcher, Aquatic Warbler, Bearded Tit.